Research on the use of virtual playing fields for monitoring various sports - Sohaib Shabbir; Zubair Hussain (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
The essential purpose of this research study is measure the use of virtual playing fields for monitoring various sports. This research study depends upon primary data analysis research measure the virtual playing fields related to the monitoring various sports. Research based on survey methods develops research questions related to the variables. for measuring the research study used smart PLS software and generate different results related to the variables. the R square, co-linearity statistic, total effects, significant analysis, also that smart PLS Algorithm model related to the use of virtual playing fields for monitoring various sports. Overall result founded that virtual playing felid is most important for monitoring various sport activities. Result also founded that there are positive and significant use of virtual playing fields for monitoring various sports